(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2024)
Purpose: Here we describe the challenges and procedures adopted to ensure safe paediatric surgery services during the COVID-19 pandemic at the paediatric surgery department in non-Covid-19 wing of Dhaka Medical College Hospital-1. Materials and Methods: Design: Retrospective study. Setting: Department of paediatric surgery in non-Covid- 19 wing of Dhaka Medical CollegeHospital-1, a tertiary care academic medical center in Dhaka, Bangladesh. Participants and duration: All patients who were admitted in the department of paediatric surgery in Dhaka Medical College Hospital-1 from March 1 through June 30, 2020. Methods: We identified patients with or without a rRTSARS- CoV-2 PCR receiving care at the department of paediatric surgery. The healthcare professionals were trained to clean, disinfect, use of PPEs, and other wastes were disposed of as per waste management protocols. Data collection & analysis: Patient data were manually abstracted from the medical record for evaluation. Responses were analysed using Microsoft Excels & SPSS, and presented as categorical data and percentages. Main outcome measures: We describe patient characteristics including demographics, presenting symptoms, type of treatment (Surgery vs Non Surgery), outcomes (morbidity & mortality), hospital stay, and distance travelled for treatment. Results: A total of 320 paediatric surgical patients were included in this study, among all patients about 66.87% patients were male child and 79.06% patients required surgeries. There were 5 patients with confirmed COVID- 19, who were transferred to the Covid-Surgical unit. During this period, there were 4 (1.25%) children who died due to non-COVID related causes. In surgical group only 24(7.5%) patients developed postoperative complications. Length of hospital stay of 44 (13.75%) of non-surgical patients were less than 72 hours, whereas 141 (40.06%) of surgical patients were more than 72 hours. Majority of patients of both groups travelled more than 100 km distance for treatment. Conclusions: This corona crisis has provided an opening for rational health care and formulating global policies. So that in future such pandemics can be tackled more carefully and consistently with advancing knowledge and better preparation. Journal of Paediatric Surgeons of Bangladesh (2019) Vol. 10 (1 & 2): 15-21